Pengaruh Rasio Likuiditas dan Rasio Solvabilitas terhadap Rasio Profitabilitas pada Perusahaan Sub Sektor Otomotif dan Komponen yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Arum Kesuma Wardani; Elmira Siska (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Along with economic recovery and fiscal stimulus, the automotive industry is starting to show a recovery trend. The purpose of this study was to determine the effect of liquidity ratios and solvency ratios on profitability in automotive sub-sector companies and components listed on the Indonesia Stock Exchange for the 2019- 2023 period. The method used in this research is quantitative with a descriptive approach using secondary data in the form of financial reports of companies listed on the Indonesian stock exchange for the 2019-2023 period. The data collection technique used in this study is the documentation technique, namely by collecting secondary data in the form of the company's annual financial statements obtained from the official website of the Indonesian stock exchange and the official website of each company. The results of the study based on partial tests show that Current Ratio has no significant effect on ROA with a t value < t table, namely 0.255 < 2.02439 and a significant value of 0.800> 0.05 and partially Debt to Equity Ratio has a negative and significant effect on ROA with a t value < t table, namely -2.336 < 2.02439 and a significant value of 0.25 < 0.05. Meanwhile, based on the simultaneous test, Current Ratio and Debt to Equity Ratio simultaneously have a positive and significant effect on the Return On Asset (ROA) variable with the value of t count> t table, namely 3.518> 3.25 and a significant value of 0.040 <0.05.